Scale effect on mean pressures: study of two reduced models of a ski jump spillway - João Gerdau de Borja; Daniela Guzzon Sanagiotto; Marcelo Giulian Marques; Alba Valéria Brandão Canellas; Cassius Palauro (Revista Brasileira de Recursos Hídricos, 2019)
ABSTRACT The ski jump type spillway is present in large Brazilian dams. After the operation of this type of spillway, a scour hole is originated downstream of the spillway toe, complementing the energy dissipation system, because the jet is cushioned by the waterbed. As the excavation of the scour hole evolves, its shape changes, with the induction of different behaviors of the jet flow within the waterbed. The importance of this scientific study is due to the fact that scour holes downstream of ski jump spillways are in constant transformation, which can cause changes in the patterns of dynamic pressures caused on the bottom. Unexpected erosions can cause instability in the submerged slopes of the pit, jeopardizing the foundation of the dam. In this work it was proceeded physical experiments, by sectional modeling (2D), in two reduced models of 1:50 and 1:100 scales, considering two stages of erosion depths in solid bottom (fixed). It was analyzed the impact site of the jet flow on the bottom, which has the major mean dynamic pressure. As result, it was possible to identify the scale effect in the pressure coefficient between the two models tested, which allowed the adjustment of trend lines that aid to estimate the pressures that occur in prototypes, increasing safety in operation of ski jump spillways.